PENDIDIKAN ISLAM DAN BUDAYA PERSPEKTIF KH. ABDURRAHCMAN WAHID - Rufi’ah Rufi’ah; Saman Hudi (Program Studi Pendidikan Agama Islam, 2024)
This research examines Abdurrahman Wahid (Gus Dur)'s views on the role and position of religion and culture in the life of the Indonesian nation, with an emphasis on the concept of